Quality in the electronic governance system - AL-IMARAH, Ahmed A.; Ibrahim, Adnan Mahmoud (International Journal of Psychosocial Rehabilitation, 2020)
The issue of electronic governance is one of the important topics that have attracted the attention of various international organizations, including production and service, due to the success achieved by applying electronic governance in the public and private sectors. In addition, governments have launched a large number of initiatives to implement e-governance in an attempt to achieve good governance. Therefore, this study considers the most important dimensions and principles of quality that must be included in e- governance systems to achieve success in their application. The present study conducts a number of official interviews with experienced and specialized personnel in providing governmental services in the Iraqi Ministry of Health to benefit from professional experience in the field of work, as well as a review of the literature and the most important studies related to the two study variables.